The Potential of Virtual Reality Technology in Children's Learning Success - Andryani, Ria; Gernowo, Rahmat; Negara, Edi Surya (Universitas Jambi, Indonesia, 2024)
Learning technology for children often does not have a positive impact on improving children's learning abilities and achievements. So that an appropriate approach is needed for the development of learning technology for children. The article examined the application and implications of the success of virtual reality-based learning for children from the perspective of human-computer interaction. This study used a literature study method from previous scientific publications regarding the potential of virtual reality technology for children's learning success. This literature review was conducted using an exploratory approach. The results of the literature study showed that various studies had been conducted in this domain, the main direction in development is the user-centered design and participatory design approach with the principles of child-computer interaction (CCI).